KEMAHIRAN BERFIKIR ARAS TINGGI (KBAT) FOR PENDIDIKAN SAINS TAHUN 1 THROUGH INTERACTIVE MOBILE APPLICATIONS - Ab Ghani, Zuriani (Journal of Computing Technologies and Creative Content, 2019)
Teaching and learning in the classroom nowadays is no longer attractive for students, especially for classes that only refers to the textbook and activity book provided by Kementerian Pelajaran Malaysia (KPM). The book is in black and white and the use of LCD has been forgotten, so there is no interesting part that can attract students to pay more intention in the classroom and love what they learn. This will affect the performance of the students especially when they learn science, because the subject has many graphics and practical characteristics that need to be understood in detail by the students. Besides that, parents also face a problem in teaching the subject due to the lack of ideas on how to make the lesson and the topic become more understandable and interesting to the students at home. Therefore, an interactive application was designed to help students, and even parents in the teaching and learning process by implementing an interactive mobile application named Interactive Mobile Application for Pendidikan Sains Tahun 1 (KBAT). The Instructional System Design (ISD) framework that is used throughout the project is the ADDIE Model. It consists of analysis, design, development, implementation and evaluation phases. The application is developed primarily using Adobe Flash Professional. The application includes the activities science that can student answering the question exactly same with the textbook activities that incorporate multimedia elements and provide interactive learning presentation. This application really helps parents to monitor their children’s improvement in learning at home.